Bond Sttrength Of Orthodontıc Dırect-Bondıng Brackets To Varıous Forces - Semra Ciğer; İlken Karatan Kocadereli (Galenos Yayinevi, 1991)
Shear and rotation are the types of forces which are used frequently during debonding, after completing the fixed-orthodontic treatment This study is carried on in vitro, in order to compare and contrast these two different forms of forces which were applied on and transmitted to the teeth. At the beginning of the process, 32 premolars extracted for orthodontic reasons, were embeded in self-curing acrylic blocks. Then, premolar brackets were bonded on each teeth under equal conditions. The teeth were put into water at 37°C for 24 hours and were seperated into two groups consisting of 16 teeht each. Shear and rotational bonding forces were applied on the first and the second groups relatively, using Instron Universal testing machine. Both the bracket and tooth surfaces were examined under the stereomicroscope (x20) and the results were evaluated using biostatistical methods. The study showed that there was three times as much force per cm2 with shear bond strength as compared to rotational bond strength. However, there was 50 % residual adhesive with the rotational bond strength.